2020
DOI: 10.1177/0020852320936750
|View full text |Cite
|
Sign up to set email alerts
|

Transparency and the efficiency of multi-actor decision-making processes: an empirical analysis of 244 decisions in the European Union

Abstract: Studies into decision-making suggest the existence of a tension between transparent and efficient decision-making. It is assumed that an increase in transparency leads to a decline in the efficiency of decision-making processes; however, this assumption has not been tested empirically. This study provides a starting point for investigating the complex relationship between transparency and efficiency on a set of 244 European Union legislative processes between 2014 and 2019. It finds that transparency neither s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The provision of transparent and readily accessible information serves as a deterrent against corrupt practises and the misuse of authority [15]. Decisions that are characterised by transparency have the potential to be more effectively scrutinised and evaluated by stakeholders [16]. Furthermore, the promotion of good governance also serves to foster increased engagement of the general public in the decision-making processes pertaining to public management.…”
Section: Resultsmentioning
confidence: 99%
“…The provision of transparent and readily accessible information serves as a deterrent against corrupt practises and the misuse of authority [15]. Decisions that are characterised by transparency have the potential to be more effectively scrutinised and evaluated by stakeholders [16]. Furthermore, the promotion of good governance also serves to foster increased engagement of the general public in the decision-making processes pertaining to public management.…”
Section: Resultsmentioning
confidence: 99%
“…One possible reason could be that understanding the advantages of transparency, participation and collaboration takes some time. However, given the doubts surrounding this issue, the relationship of transparency and openness policies with trust and legitimacy should be addressed in future research, as already suggested by Brandsma and Meijer (2020) and Grimmelikhuijsen et al (2020).…”
Section: Political Parties' Decision-making and Collaborationmentioning
confidence: 93%
“…Particularly in Coreper 1, some presidencies are instructed vigorously from their capitals, reducing their flexibility (R94). But ministerial involvement appears quite common: in the 2014-2019 EP term, for 249 files a trilogue procedure has been started (Brandsma & Meijer, 2020), and the Council's document register shows that for 89 of these a general approach was adopted prior to negotiations, which is 36 per cent.…”
Section: A Focused-structured Analysismentioning
confidence: 99%